(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The research aims to identify the concept of geopolitical risks, and the state of cooperation between risk management and internal audit together to overcome geopolitical uncertainty, and to draw the attention of internal auditors to the ways that internal audit can provide assessment, confirmation and advice with regard to geopolitical risks, including responses initiatives and regulatory penalties. To achieve the objectives of the research, the researcher used the constructive approach in the study and analysis through the use of dissertations master’s theses, periodicals, books and websites that deal with the subject of the study, especially with regard to the areas of: geopolitical risks and the role of internal audit in assessment, confirmation and advice. The research problem is defined by the basic question that this research seeks to answer: Can internal audit provide assurance and advice on geopolitical risks? And how? The research reached a set of conclusions, the most important of which are: The need of the internal auditor to carry out a comprehensive and independent assessment of geopolitical risks in cooperation and consultation with the Risk Management in order to identify the most important risks and integrate them into the audit plan, and to amend the plan based on the results of the continuous assessment and emerging risks, and to ensure that the management and the audit committee are fully aware of these risks and their effects and that they take the appropriate measures to deal with it and address it in a timely manner. Based on the research findings, proposals were made that are consistent with these conclusions, the most important of which are: The need for parties interested in the internal audit profession to hold seminars for auditors and hold specialized workshops to introduce geopolitical risks, and to draw the attention of internal auditors to the ways in which internal audit can provide assessment, confirmation and advice, with regard to geopolitical risks, and they are considered an essential part of the task of the successful internal auditor who adds Valuable to the company that gave him its trust.